The European Union Should Not Ignore the Female Face of Forced Labour - Aleydis Nissen (Oslo Law Review)
This article discusses the European Commissionʼs proposal for a regulation to ban products from forced labour in the European Union (EU) of September 2022. It argues that the Commission failed to conduct an impact assessment which could have addressed gender dimensions. This was omitted because the proposal would be ʻurgentʼ. While not atypical—the EU has often turned a blind eye to womenʼs issues—the gender-blind nature of the proposal is unfortunate. At least three indicators of forced labour that are used by the International Labour Organization—including the two most common indicators vulnerability and wage non-payment—have a differentiated impact on women. Drawing from the three-step framework in the Gender Guidance of the United Nations Working Group on Business and Human Rights, this article suggests a way to start discussions to include a gender perspective in the regulation.